Exploration of the Relationships Among Narcissism, Life Satisfaction, and Loneliness of Instagram Users and the High- and Low-Level Features of Their Photographs - Kim, Yunhwan; Nan, Dongyan; Kim, Jang Hyun (Frontiers in Psychology, 2021)
We examined the associations between Instagram user characteristics and the features of their photos. Narcissism, life satisfaction, and loneliness were employed for user variables and the features at high (content) and low (pixel) levels were employed to analyze Instagram photos. An online questionnaire of 179 university students was conducted and their Instagram photos, 25,394 in total, were collected and analyzed. High-level features were extracted using Computer Vision and Emotion APIs in Microsoft Azure Cognitive Services, and low-level features were extracted utilizing the program written by the authors. The results of correlation analysis indicate that narcissism, life satisfaction, and loneliness were significantly associated with a part of photo features at high and low levels. Also, the results of predictive analysis suggest that narcissism, loneliness in total, and social loneliness could be predicted with acceptable accuracy from Instagram photo features, while life satisfaction, family loneliness, and romantic loneliness could not. Implications of this research and suggestions for further research were presented.